2013
DOI: 10.1177/0957650913498735
|View full text |Cite
|
Sign up to set email alerts
|

Development of a wood-fired cooking stove to incorporate a thermo-acoustic engine-generator unit

Abstract: Citation: Dennis, R. and Pullen, K. R. (2013). Development of a wood-fired cooking stove to incorporate a thermo-acoustic engine-generator unit. Proceedings of the Institution of Mechanical Engineers, Part A: Journal of Power and Energy, 227(7), pp. 740-751. doi: 10.1177/0957650913498735 This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent AbstractThe provision of affordable electrical power in off-grid rural areas of developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Thermoacoustic engines can be integrated into efficient wood cooking stoves to provide electricity while cooking [39], but the output and efficiency have to date proven to be too low [32]. Recent social science studies have suggested that an ideal system would generate about 100 W of electrical energy and cost less than $100, and even 20 W conveys considerable benefits [40].…”
Section: Externally Fired Gas Turbine (Efgt)mentioning
confidence: 99%
“…Thermoacoustic engines can be integrated into efficient wood cooking stoves to provide electricity while cooking [39], but the output and efficiency have to date proven to be too low [32]. Recent social science studies have suggested that an ideal system would generate about 100 W of electrical energy and cost less than $100, and even 20 W conveys considerable benefits [40].…”
Section: Externally Fired Gas Turbine (Efgt)mentioning
confidence: 99%
“…City University (one of the consortium members) has developed a highly efficient stove, called SCORE-1, as described by Dennis and Pullen. 5 This stove incorporates the outcome of research on the combustion chamber design. Practical Action has tested this stove design in Kenya and Nepal as part of its research and dissemination activities in the field 6 and has promoted other improved stove designs.…”
Section: Introductionmentioning
confidence: 99%